A Study of Concepts on Ratio Matter Learning Unit and Problem-Solving Ability Using Concrete-Pictorial-Abstract Approach of Grade 7 Student - Kleunthaisong, Thanthida; Keeratichamroen , Wasana (Ratchaphruek Journal, 2023)
This research was to study the concept and problem-solving ability using concrete-pictorial-abstract approach. The purposes of this study were to: 1) Compare students’ concept on ratio matter before and after learning; 2) Compare students’ concept between after learning and the 70 percent criterion; and 3) Compare students’ problem solving ability before and after learning. The sample group of this study were 25 grade 7students in the second academic year of 2022 Banchaimongkol Suebsin Witthaya School. The research instruments were 5 lesson plans using concrete-pictorial-abstract approach, the ratio matter concepts test and problem solving ability test. The data were analyzed by percentage, mean, standard deviation, and t-test for paired sample and t-test for one sample statistic. The findings of this research were: 1) Comparison of concepts on ratio matter of grade 7 students before and after learning using concrete-pictorial-abstract was found that after learning was higher than before learning management with statistical significance at .05 level. 2) Concepts on ratio matter of grade 7 students after learning using concrete-pictorial-abstract was lower than the 70 percent criterion with statistical significance at .05 level. 3) Problem solving ability of grade 7 students after using concrete-pictorial-abstract was significantly higher than before learning at the .05 level.